Developing a mobile app as a communication aid for the Deaf people of Cyprus - Pieri, Katerina (2017)
Communication is still a barrier for people with severe to profound hearing loss. Deaf people face communication problems in their everyday lives and those problems are primarily associated with the use of different languages between them and Hearing people. Their inability to hear as well as their reliance on sign language often stands as an obstacle to their expression and reception of spoken language. Cyprus ranks amongst the top five European countries with regard to the percentage of population who are Deaf (0.12% of the population). However, the Deaf Community of Cyprus does not receive any technological or financial support from the Information society and the Government of Cyprus respectively. Despite advances in communication aid technologies, there is no technology to support the Cypriot Sign Language (CSL) and offer real-time speech to sign language conversion to the Deaf people of Cyprus. Through this study, the communication needs and requirements of the Cypriot Deaf people were explored based on which, an interactive prototype of a mobile app was developed and evaluated with Deaf users. The study identified how a mobile app can help them to communicate more effectively with hearing people and what significant features the app should have. Action Research methodology in combination with User-Centred Design were implemented for the completion of the project. Multiple methods were used for both the data collection and evaluation processes to enable the data to be triangulated and the results to be validated. Through the data collection, it was observed that more than half of the participants experience reading and writing difficulties and their requirements differed from the participants who do not experience such difficulties. Two user personas and scenarios were created to describe the goals and motivations of the users and to enable empathetic design solutions to be developed. Medium fidelity prototypes were used in two participatory design sessions to allow the Deaf users to be involved in the design of the mobile app. The evaluation of the final interactive prototype showed that 100% of the users (N = 8) found the app particularly useful and they were completely satisfied with it. The use of CSL videos of a real person interpreting the hearing people’s speech in real-time as well as the custom onscreen keyboard were the most liked features of the mobile app. Finally, the experiment showed that the mobile app has a great potential to save more than one third of the time spent while trying to perceive the speech of a hearing person.